210Po and 210Pb as Tracers of Particle Cycling and Export in the Western Arctic Ocean - Bam, Wokil; Maiti, Kanchan; Baskaran, Mark (Frontiers in Marine Science, 2021)
The distribution and vertical fluxes of particulate organic carbon and other key elements in the Arctic Ocean are primarily governed by the spatial and seasonal changes in primary productivity, areal extent of ice cover, and lateral exchange between the shelves and interior basins. The Arctic Ocean has undergone rapid increase in primary productivity and drastic decrease in the areal extent of seasonal sea ice in the last two decades. These changes can greatly influence the biological pump as well as associated carbon export and key element fluxes. Here, we report the export of particulate organic and inorganic carbon, particulate nitrogen and biogenic silica using 210Po and 210Pb as tracers for the seasonal vertical fluxes. Samples were collected as a part of US GEOTRACES Arctic transect from western Arctic Basin in 2015. The total activities of 210Po and 210Pb in the upper 300 m water column ranged from 0.46 to 16.6 dpm 100L–1 and 1.17 to 32.5 dpm 100L–1, respectively. The 210Pb and 210Po fluxes varied between 5.04–6.20 dpm m–2 d–1 and 8.26–21.02 dpm m–2 d–1, respectively. The corresponding particulate organic carbon (POC) and particulate nitrogen (PN) fluxes ranged between 0.75–7.43 mg C m–2 d–1 and 0.08–0.78 mg N m–2 d–1, respectively, with highest fluxes observed in the northern ice-covered stations. The particulate inorganic carbon (PIC) and biogenic silica (bSi) fluxes were extremely low ranging from 0 to 0.14 mg C m–2 d–1 and 0.14 to 2.88 mg Si m–2 d–1, respectively, at all stations suggesting absence of ballast elements in facilitating the biological pump. The variability in POC fluxes with depth suggest prominent influence of lateral transport to downward fluxes across the region. The results provide a better understanding of the spatial variability in the vertical fluxes POC, PN, bSi, and PIC in the western Arctic which is currently undergoing dramatic changes.